Cost of Vacancy (CoV) Reduction Through Employee Upskilling for Swiss Manufacturing in Industry 5.0 - Rachman, Anastasia (Digital Repository of Theses, 2026)
Based on the theories of Human Capital, Efficiency Wage, and Skill-Biased Technological Change, this doctoral dissertation examines the strategic role of employee upskilling in reducing turnover and the Cost of Vacancy (CoV) within Swiss manufacturing firms in the Industry 5.0 era. Industry 5.0 represents a new phase of industrial transformation that emphasises human–machine collaboration, resilience, and sustainable growth. Despite the proliferation of workforce development programs, many firms continue to treat them as costs rather than strategic investments, leaving limited empirical evidence on how upskilling impacts key operational outcomes, particularly vacancy cost reduction. This study addresses this gap by developing and validating a CoV model that quantifies the economic impact of upskilling initiatives. It investigates how investments in technical and cognitive skills influence workforce stability, retention, and organisational competitiveness. Employing a mixed-methods approach, the research integrates quantitative data from 100 employees in a Swiss manufacturing firm with qualitative insights from managers, capturing both measurable outcomes and contextual organisational practices. The results of this study indicate that structured upskilling programs reduce vacancy-related costs by approximately 35%, primarily through enhanced internal skill coverage, improved employee engagement, and reduced turnover intention. Regression analysis demonstrates that upskilling accounts for 36% of the variance in Perceived Cost of Vacancy (PCoV), highlighting its substantial role in mitigating both perceived and monetized vacancy impacts. Employees who participated in multi-skilled, Industry 5.0– oriented training exhibited greater adaptability and role flexibility, enabling teams to maintain operational continuity during vacancy periods without relying on immediate external recruitment. Moreover, mediation analysis confirms that engagement partially explains this relationship (indirect effect β = -0.24), indicating that upskilling strengthens motivational and behavioural mechanisms that reduce turnover-related disruptions. Collectively, these findings underscore the financial and strategic value of investing in employee development, positioning upskilling as a central driver of workforce resilience and cost efficiency in Swiss manufacturing firms operating in Industry 5.0 environments. This dissertation contributes to the human capital and organisational management literature by providing a validated framework linking upskilling to operational efficiency and resilience. It offers actionable insights for manufacturing leaders seeking to leverage workforce development as a strategic tool to enhance competitiveness and sustain innovation in Industry 5.0. The findings underscore that upskilling is not merely a developmental activity but a critical driver of organisational stability, productivity, and long-term growth. Keywords: Industry 5.0, upskilling, human capital, Cost of Vacancy (CoV), turnover, Swiss manufacturing, workforce development, employee retention, organisational resilience.